2021
DOI: 10.3390/cancers13071688
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ERBB Family Members as Predictive Markers of Prostate Cancer Progression and Mortality

Abstract: Background: EGFR, ERBB2, ERBB3, and ERBB4 are growth receptors of the ERBB family implicated in the development of epithelial cancers. Studies have suggested a role for EGFR and ERBB3 in the development of prostate cancer (PC), while the involvement of ERBB2 and ERBB4 remains unclear. In this study, we evaluated the expression of all members of the ERBB family in PC tissue from a large cohort and determined their contribution, alone or in combination, as prognostic markers. Methods: Using immunofluorescence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The EGFR/ERBB4, MET and IGF-1R families of growth factor receptor have been implicated in prostate cancer [ 31 , 68 , 69 ]. Receptors of the EGFR/ERBB family are tightly correlated with poor prognosis, drug resistance, cancer metastasis, and lower survival rate of prostate cancer patients [ 68 , 70 ]. Overexpression of ligands and/or receptors of ERBB and MET pathways has been reported in prostate cancer [ 69 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR/ERBB4, MET and IGF-1R families of growth factor receptor have been implicated in prostate cancer [ 31 , 68 , 69 ]. Receptors of the EGFR/ERBB family are tightly correlated with poor prognosis, drug resistance, cancer metastasis, and lower survival rate of prostate cancer patients [ 68 , 70 ]. Overexpression of ligands and/or receptors of ERBB and MET pathways has been reported in prostate cancer [ 69 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein-protein interaction networks analysis of deleterious genes and the VUS-containing genes in the PI3K-Akt signaling pathway revealed that these two groups of genes interacted closely with each other in both cohorts by the nodes of ERBB family (EGFR, ERBB2 and ERBB3), BRCA1, HRAS, and TP53. A recent study revealed that the combined protein expression patterns of EGFR, ERBB2, and ERBB3 were associated with a higher risk of progression and mortality in prostate cancer [ 72 ]. HRAS, as one of the Ras oncogene family, was found to have increased amplification rate in hormone-resistant prostate cancer compared with hormone-sensitive prostate cancer [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of KRT7 expression was assessed in a cohort of radical prostatectomy specimens ( n = 285 patients) from well-balanced localized PC with clinical/ pathological characteristics detailed in Supplementary Table S1 [ 24 , 25 ]. The incidence of biochemical recurrence (BCR) at 5 years was 33% (94 patients), and 9.8% (28 patients) of the cohort had an onset of bone metastasis leading in 6.3% of cases (18 patients) to a prostate-cancer specific death.…”
Section: Resultsmentioning
confidence: 99%
“…This TF123 was composed of a total of six TMA blocks. For each patient, 2 adjacent benign duplicate 0.6 mm cores and 2 tumoral duplicate cores were available, as previously published [ 24 , 25 ]. The composition of the cohort is described in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation